Two Stage Revision Total Hip Arthroplasty; A Case Report - Hari Om Aggarwal; Nitish Kohli; Harish Bansal; Ajay Sharma (GMC Patiala Journal of Research and Medical Education, 2020)
Infected Total Hip Prosthesis is one of the most serious complication of total hip arthroplasty (THA) and can have serious consequences. Several techniques for treating infected THA , have been reported recently. These techniques include antibiotic suppression, debridement, and closed continuous irrigation without removing the prosthesis; one-stage cemented revision THA using antibiotic-impregnated cement; and two stage revision THA using either a cemented or a non-cemented component. We here report the management case of a infected total hip prosthesis in a obese 38yr male patient by two stage revision total hip arthroplasty, using an antibiotic impregnated cement spacer for the interval between first and second stages.